Mantle source heterogeneity, magma generation and magmatic evolution at Terceira Island (Azores archipelago): Constraints from elemental and isotopic (Sr, Nd, Hf, and Pb) data - Madureira, Pedro (2012)
This work addresses the present-day (b100 ka) mantle heterogeneity in the Azores region through the study of two active volcanic systems from Terceira Island. Our study shows that mantle heterogeneities are detectable evenwhen “coeval” volcanic systems (Santa Bárbara and Fissural) erupted less than 10 km away. These volcanic systems, respectively, reflect the influence of the Terceira and D. João de Castro Bank end-members defined by Beier et al. (2008) for the Terceira Rift. Santa Bárbara magmas are interpreted to be the result of mixing between a HIMU-type component, carried to the upper mantle by the Azores plume, and the regional depleted MORB magmas/source. Fissural lavas are characterized by higher Ba/Nb and Nb/U ratios and less radiogenic 206Pb/204Pb, 143Nd/144Nd and 176Hf/177Hf, requiring the small contribution of delaminated sub-continental lithospheric mantle residing in the upper mantle. Published noble gas data on lavas from both volcanic systems also indicate the presence of a relatively undegassed component, which is interpreted as inherited from a lower mantle reservoir sampled by the ascending Azores plume. As inferred from trace and major elements, melting began in the garnet stability field, while magma extraction occurred within the spinel zone. The intra-volcanic system's chemical heterogeneity is mainly explained by variable proportions of the above-mentioned local end-members and by crystal fractionation processes.